Paradigmatic reflections on media, culture and public relations : Paradigmatska promišljanja o kulturi medija i odnosima s javnostima - Plenković, Mario (Array, 2020)
The paper reports on some of the research results and achievements on international scientific projects: "Croatian media communication in a convergent environment" (Faculty of Graphic Arts, University of Zagreb, Zagreb, Croatia) and "Strategic Communication Management" (Alma Mater Europaea - EASA, Maribor, Slovenia). The aim of this research work is a paradigmatic presentation and publication of separately selected thematic media research paradigms in a systematic paradigmatic communication chain that affirms culture, media and public relations (Case study: "Media, Culture and Public Relations" (2012-2020)). The paper uses qualitative and quantitative paradigmatic ontological, epistemological, axiological, rhetorical and communication research methodology. Project paradigmatic research was conducted in the time limits from 2012 to 2020. The obtained research results and conducted communication analysis of the essence and form of media communication culture and public relations is a new paradigmatic scientific contribution to the culture of media communication and the advancement of the role and function of public relations in the new inclusive information society.